Perceived barriers to digitalization by small-scale farmers Gauteng Province - Choguya, Donald (University of the Witwatersrand, Johannesburg, 2022)
Digitalization in the fourth industrial revolution era has transformed many industries across the board. However, there are some that have been affected more than the others as depicted in the digital vortex. Lagging is the agricultural sector. This study was a quantitative research study that utilized a sample of 40 small-scale farmers to be representative of the Gauteng Province small-scale farmers. The research related the perceived barriers to digitalization and its impact to the agricultural activities of small-scale farmers in Gauteng Province. The data was analysed using the multiple regression analysis and correlation coefficient. Analysis of the results showed a massive gap between small-scale farmers and commercial farmers on the adoption of digitalization. Further analysis indicated that small-scale farmers were less likely to be impacted by digitalization to adopt technological utilization. It was also found that small-scale farmers were contributors to food production. Finally, it was also discovered that small-scale farmers were less established to adapt and adopt to digitalization in their agricultural activities due to various barriers. The recommendations were that there was need to do more research to find ways to bridge the gap to digitalization between small-scale farmers in Gauteng Province and commercial farmers. So that small-scale farmers in Gauteng Province especially the small-scale farmers in rural areas could also be exposed to the digitalization of operations to enable them to improve production
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: South Africa; Gauteng Province; Small-scale farmers; Digitalization; Perceptions; Gross Domestic Product; Stakeholders; UCTD; SDG-9: Industry, innovation and infrastructure